Comprehensive review on pharmacological effects and mechanism of actions of taxifolin: A bioactive flavonoid - Shweta Jain; Ankur Vaidya (Elsevier, 2023)
Introduction: Uses of flavonoids have been increased tremendously in the past few years to offer prevention, relief, and to cure a variety of diseases. Taxifolin (TAX), a flavonoid, belong to subcategory flavanone is a dihydroquercetin, possesses numerous pharmacological activities. Methods: An extensive literature survey utilizing electronic database such as Google Scholar, Pubmed and Scopus up to 2022 was performed to obtain the sources and chemical structure of TAX. The search data were explored to conclude the pharmacological activity and mechanism of action of TAX. Results: TAX occurs naturally in citrus fruits, onion, and many other plants including Siberian larch, Pseudotsuga taxifolia, Taxus chinensis var. mairei and Pinus roxburghii as well as marketed under the trade name of Venoruton®, Legalon™ and Pycnogenol™. Numerous studies have been reported to confirm pharmacological activities of TAX. Studies scientifically proven the beneficial effects of TAX against variety of diseases and recommended for the treatment of bacterial infection (including acne and toxoplasmosis), cardiovascular diseases, inflammation, cancer diseases, viral infections, Alzheimer, diabetes, allergic reaction, immunodeficiency etc. TAX also inhibits several enzymes, including, tyrosinase, angiotensin converting enzyme (ACE), diacylglycerol acyltransferase (DGAT), microsomal triglyceride transfer protein (MTP), and so forth. Moreover, nanoparticle formulations of TAX provide improved bioavailability, sustained release and better antioxidant activity. Conclusion: The present review describes numerous biological and enzymatic activity of TAX and also explores the functional features of TAX responsible for these activities.